Staphylococcus simulans endocarditis of native aortic and mitral valves. Case report and literature review. (October 2020) - Power, N.; Calisti, G.; Price, F.; Watt, V.; Gamlin, W.; Dobson, L.E.; Ray, S.G.
Highlights: Coagulase negative staphylococci (CoNS) can cause significant human disease. Staphylococcus simulans can share many virulence factors with Staphylococcus aureus . S. simulans can cause a destructive endocarditis similar to S.aureus . Exposure to domesticated animals may result in colonisation by S. simulans . All reported cases of S. simulans endocarditis have affected native cardiac valves. S. simulans can be detected by 16s PCR. Abstract: Staphylococcus simulans is a coagulase-negative Staphylococcus species that is a commensal of domestic animals. We report the case of a 58 year old man with an aggressive form of S. simulans endocarditis involving native aortic and mitral valves, and the aortic root. Blood cultures were positive for S. simulans on presentation. The presence of S. simulans was confirmed by 16S PCR of the explanted aortic valve. Due to development of paravalvular leak causing left sided heart failure, and of a large thrombus in the left ventricle the patient required further surgery with replacement of the metallic valves with bio-prosthetic valves two months after the initial surgery. He died shortly after the re-do operation due to due to gram negative sepsis and cardiogenic shock. In addition to our case, we summarise the clinical presentation and outcome of the four additional cases of S. simulans endocarditis described in the literature to date. We also report virulence factors associated with other S. simulans isolates. The aim of this case report and literature review is to highlight the potentially increased pathogenicity of S. simulans .